The Role Of Paramedics In The Prompt Identification And Treatment Of Acute Myocardial Infarction (The Review of Diabetic Studies, 2025)
Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality worldwide. Early identification and treatment are crucial for improving patient outcomes. Paramedics play a pivotal role in the prehospital management of AMI, serving as the first point of contact in the healthcare system. This review explores the multifaceted role of paramedics in the prompt recognition and management of AMI. Paramedics are trained to rapidly assess patients with suspected AMI using clinical history, physical examination, and 12-lead electrocardiography (ECG). Their ability to accurately interpret ECGs and identify ST-segment elevation myocardial infarction (STEMI) is critical for initiating timely reperfusion therapy. Prehospital pharmacological interventions, such as aspirin, nitrates, and analgesics, are administered by paramedics to stabilize patients and alleviate symptoms. In certain systems, paramedics can also perform prehospital thrombolysis, significantly reducing time to treatment. Paramedics make crucial transport decisions, prioritizing direct transfer to percutaneous coronary intervention (PCI) capable centers when appropriate. Prehospital notification of receiving hospitals allows for activation of catheterization laboratories and minimizes door-to-balloon times. Challenges in prehospital AMI management include atypical presentations, limited diagnostic tools, and geographical and logistical barriers to timely care. However, advances in portable diagnostic devices, digital ECG transmission, and artificial intelligence-assisted triage systems are enhancing paramedics' capabilities. The expanding role of community paramedicine also positions paramedics as key providers in preventive cardiac care and early detection of AMI. Ongoing training, protocol development, and integration with healthcare systems are essential for optimizing paramedics' impact on AMI care and patient outcomes.